It's Time to Go Green with Pride: A Conceptual Study of Green Marketing - Pillai, Raji Parameshwaran (Indian Journal of Marketing, 2013)
Purpose: The purpose of the paper is to discuss the subject of 'concern for the environment' in depth and to discuss how each one of us can contribute towards conservation of ecology. The paper aims to find out how the concern can be brought to the notice of the people who can bring in the much needed change, to look into the hurdles in way of effective implementation of the 'going green' campaign, to highlight the responsibility of change makers like the marketers, the consumers and the corporate bodies towards 'going green'. Methodology/Approach: The paper studies the components of green marketing theory. The paper studies the theory presented by the researchers in the field of ecological management, which includes green marketing, eco-friendly products, ecological processes. Time frame: The research study was conducted during the period of November 2011 to April 2012. Value: The paper concludes with a set of action steps that need to be taken to inculcate the concern for ecology by bringing in a sense of becoming a valuable conserver of ecology.